2016
DOI: 10.1007/s10068-016-0192-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of phage-antibiotic combination in reducing antibiotic resistance in Staphylococcus aureus

Abstract: This study was designed to evaluate the effect of phage-antibiotic synergy in reducing antibiotic resistance. The initial numbers of treated with ciprofloxacin, phages, and combination were significantly reduced by 3.47, 4.62, and 5.75 log CFU/mL, respectively, at the early 12 h of incubation. The combination treatment most effectively inhibited the growth of, showing more than 4 log reduction in 18 h of incubation at 37°C. The significant reduction in biofilm formation by was observed at the combination treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…This strategy exerts a heavy selective pressure on the targeted bacteria which induces a heavier fitness cost to them. This cost would drive resistant mutants eventually appearing towards being fitter to resist to the phage and antibiotic and less fit to reproduce and infect their hosts (Torres-Barceló et al, 2014;Jo et al, 2016).…”
Section: Giving a Second Chance To Antibiotics With Phage-antibioticmentioning
confidence: 99%
“…This strategy exerts a heavy selective pressure on the targeted bacteria which induces a heavier fitness cost to them. This cost would drive resistant mutants eventually appearing towards being fitter to resist to the phage and antibiotic and less fit to reproduce and infect their hosts (Torres-Barceló et al, 2014;Jo et al, 2016).…”
Section: Giving a Second Chance To Antibiotics With Phage-antibioticmentioning
confidence: 99%
“…For a Siphoviridae phage used in the study, the effect which can be defined as completely synergistic was reported to be observed only after a 300 min incubation ‐ (Knezevic, Curcin, Aleksic, Petrusic, & Vlaski, ). Synergistic antimicrobial efficacy of phages with antibiotics against S. aureus was evaluated in another study where the obtained results showed that the synergism between phage and antibiotic was more prominent in S. aureus KACC 13236 strains treated with SA11 phage in the presence of cefoxitin, chloramphenicol, and polymyxin (Jo, Kim, Ding, & Ahn, ). It was also stated that the cells were all damaged or killed as a result of applying the combined treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, studies involving the interaction of bacteriophages with various components have been frequently found in the literature. The majority of these studies are based on phage-antibiotic synergism and the elimination of biofilms (Chaudhry et al, 2017;Nouraldin et al, 2016) or bacteria such as Acinetobacter baumannii (Jansen et al, 2018), Money, 2017), Pseudomonas aeruginosa (Lin et al, 2018;Uchiyama et al, 2018), S. aureus (Jo, Kim, Ding, & Ahn, 2016). There are also studies examining the interaction of phages with different agents such as honey (Oliveira et al, 2017) or disinfectants (Agún et al, 2018).…”
Section: S Aureusmentioning
confidence: 99%
“…Disks of erythromycin (15 μg) and vancomycin (30 μg) were placed on the Mueller-Hinton agar plates containing S. aureus (105CFU/mL) alone and with phage (106 PFU/mL). After 18-h incubation at 37° C, the diameter of the clear inhibition zone was measured (Jo et al, 2016) 3. Results…”
Section: Disk Diffusion Susceptibility Testmentioning
confidence: 99%